A Feminist Companion to the Posthumanities (Springer International Publishing, 2018)
This companion is a cutting-edge primer to critical forms of the posthumanities and the feminist posthumanities, aimed at students and researchers who want to catch up with the recent theoretical developments in various fields in the humanities, such as new media studies, gender studies, cultural studies, science and technology studies, human animal studies, postcolonial critique, philosophy and environmental humanities. It contains a collection of nineteen new and original short chapters introducing influential concepts, ideas and approaches that have shaped and developed new materialism, inhuman theory, critical posthumanism, feminist materialism, and posthuman philosophy. A resource for students and teachers, this comprehensive volume brings together established international scholars and emerging theorists, for timely and astute definitions of a moving target - posthuman humanities and feminist posthumanities.